Trend Analysis of Climate Change across Nigeria: A Mann-Kendall and Sen’s Approach - E. E. Iyeme; U. J. Ekah; A. O. Njok; E. P. Agbo; G. C. Offorson (Archives of Current Research International, 2024)
This study investigates the long-term variations in temperature and precipitation across Nigeria’s climatic zones, focusing on their impact on agriculture and water resources. Using data from Calabar, Ibadan, Kano, and Kukawa to represent the tropical monsoon, tropical savannah, semi-arid and desert climate, respectively, the research adopts the Mann-Kendall trend test, innovative trend analysis, and anomaly analysis to assess climate trends and their implications. The findings reveal significant warming trends across all locations, particularly in semi-arid and desert zones like Kano and Kukawa, with temperature increase of 0.0443°C/year and 0.0412°C/year, respectively. It was further observed that precipitation trends varied by region, with Calabar showing a monthly decrease of -1.26 mm/year, while Kukawa exhibited an unexpected significant increase, which suggest potential greening in the desert. The study underscores the need for region-specific climate adaptation strategies. For instance, increased warming in semi-arid zones calls for enhanced water conservation efforts, while the rising precipitation in desert regions raises concerns about flood risks and water management. The results highlight the importance of multi-scale and spatial analysis to better inform climate-related policy decisions. National and regional policymakers must adopt targeted agricultural practices, improve water resource management, and implement climate resilience strategies to mitigate the adverse effects of these climatic shifts.